Zur Modellbildung und Simulation reibungserregter Schwingungen in Pkw-Schaltgetrieben - Jehle, Georg (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2017)
An approach for the reproduction of friction induced vibrations in shift gearboxes in audible frequency range is presented. The research's core is given by follower forces, which arise out of the sliding clutch and gear contact. Firstly, a multi-body dynamic system with few degrees of freedom is presented, which is extended step-by-step. Besides the pure analysis of the stationary solution's stability, dynamic solutions are presented and discussed.